E-Learning Adoption and Its Impact on Teaching-Learning Interactions in the Digital Era - Nur fitrah Arezky (Generasi Sains Indonesia, 2025)
This study investigates the adoption of e-learning and its impact on teaching–learning interactions in the digital era. Using a quantitative survey design, data were collected from 120 university students to measure the influence of perceived usefulness, perceived ease of use, teacher presence, peer interaction, and cognitive engagement. The results indicate that perceived usefulness and teacher presence significantly shape students’ learning experiences, while perceived ease of use plays a supportive role. Conversely, peer interaction and cognitive engagement showed weaker effects, suggesting that online learning practices remain predominantly teacher-centered. The findings highlight that effective e-learning adoption requires not only adequate technological infrastructure but also strong pedagogical strategies and active instructor involvement. This study emphasizes that e-learning adoption should be viewed as a pedagogical transformation rather than solely a technological shift, with implications for universities, educators, and policymakers seeking to optimize digital education.